2017
DOI: 10.1002/jgf2.27
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in the elderly: Diagnosis and management

Abstract: Compared with younger people, elderly people show age‐related sleep changes, including an advanced sleep phase and decreased slow‐wave sleep, which result in fragmented sleep and early awakening. Multiple etiologies contribute to insomnia in the elderly, consistent with the observation that elderly people are likely to have comorbid conditions and medications. When elderly individuals complain of insomnia, it is important to assess treatable medical conditions and medication use that may be responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
120
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(148 citation statements)
references
References 68 publications
1
120
3
6
Order By: Relevance
“…Key words: poor sleep quality; peptic ulcer disease recurrence; older patients P oor sleep quality 1 and peptic ulcer disease (PUD) 2 are both major public health problems affecting physical and psychological well-being of older adults. Poor sleep quality is partially attributable to age-related increases in comorbid conditions, medication use, and sleep behavior changes, which affect approximately one-third of older adults worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Key words: poor sleep quality; peptic ulcer disease recurrence; older patients P oor sleep quality 1 and peptic ulcer disease (PUD) 2 are both major public health problems affecting physical and psychological well-being of older adults. Poor sleep quality is partially attributable to age-related increases in comorbid conditions, medication use, and sleep behavior changes, which affect approximately one-third of older adults worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality is partially attributable to age-related increases in comorbid conditions, medication use, and sleep behavior changes, which affect approximately one-third of older adults worldwide. 1 Plausibly due to reduced prostaglandin levels and blood supply to the gastric mucosa resulting from aging, PUD formation and its recurrence are also prevalent among older adults. 3 Although Helicobacter pylori eradication therapy has effectively reduced the rate of PUD recurrence from over 40% to 5% to 25%, 4,5 recent clinical findings revealed that only a proportion of H. pylori-reinfected patients experienced PUD recurrence and that few of the PUD recurrent patients were reinfected with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of sleep for the overall health and well‐being of the elderly has been increasingly recognized . Psychiatrists, neurologists, and geriatricians, general practitioners should have sound knowledge about the changing pattern of sleep from infancy to old age.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of sleep for the overall health and well-being of the elderly has been increasingly recognized. 1,2 Psychiatrists, neurologists, and geriatricians, general practitioners should have sound knowledge about the changing pattern of sleep from infancy to old age. Additionally, the sleep problems faced by the elderly, and the consequences of inadequate and inappropriate sleep in determining the quality of their life, have gained recognition recently.…”
Section: Introductionmentioning
confidence: 99%